Ferroptosis—A Novel Mechanism With Multifaceted Actions on Stroke - Fang, Xiao-Ling; Ding, Shao-Yun; Du, Xiao-Zheng; Wang, Jin-Hai; Li, Xing-Lan (Frontiers in Neurology, 2022)
As a neurological disease with high morbidity, disability, and mortality, the pathological mechanism underlying stroke involves complex processes such as neuroinflammation, oxidative stress, apoptosis, autophagy, and excitotoxicity; but the related research on these molecular mechanisms has not been effectively applied in clinical practice. As a form of iron-dependent regulated cell death, ferroptosis was first discovered in the pathological process of cancer, but recent studies have shown that ferroptosis is closely related to the onset and development of stroke. Therefore, a deeper understanding of the relationship between ferroptosis and stroke may lead to more effective treatment strategies. Herein, we reviewed the mechanism(s) underlying the onset of ferroptosis in stroke, the potential role of ferroptosis in stroke, and the crosstalk between ferroptosis and other pathological mechanisms. This will further deepen our understanding of ferroptosis and provide new approaches to the treatment of stroke.